Staphylococcus aureus Dominates Urinary Tract Infections with Significant Antibiotic Resistance: A Cross-Sectional Study Among Hospitalized Patients - Okta Bela Canalia; Ance Roslina (UMSU, 2026)
Urinary tract infection (UTI) remains one of the most common infections, often complicated by antimicrobial resistance. In recent years, Staphylococcus aureus has been increasingly identified as a causative organism, particularly among patients with comorbidities or prolonged catheterization. This study aimed to examine the prevalence and resistance profile of S. aureus in UTI and to assess its clinical associations. A cross-sectional analytical study was conducted using retrospective data from 59 medical records of hospitalized patients diagnosed with UTI at Dr. Pirngadi General Hospital Medan, between Januari 2020 and December 2022. Bacterial identification and antibiotic susceptibility were determined from urine cultures. Statistical analysis used the Chi-square test. Staphylococcus aureus was identified as the most frequent pathogen (59.3%). Infections were more common in females and in patients aged over 60 years. S. aureus infection showed a significant association with comorbidities and catheter use (p 0.05). The organism exhibited high resistance to ceftriaxone but remained sensitive to oxacillin, linezolid, and cefazolin. S. aureus is the predominant pathogen causing UTI among hospitalized patients, with significant associations to catheter use and comorbidities, as well as notable antibiotic resistance.